How are we improving the delivery to back of the eye? Advances and challenges of novel therapeutic approaches. (3rd October 2017) - Agrahari, Vibhuti; Agrahari, Vivek; Mandal, Abhirup; Pal, Dhananjay; Mitra, Ashim K.
ABSTRACT: Introduction : Drug delivery to the back of the eye requires strategic approaches that guarantee the long-term therapeutic effect with patient compliance. Current treatments for posterior eye diseases suffer from significant challenges including frequent intraocular injections of anti-VEGF agents and related adverse effects in addition to the high cost of the therapy. Areas covered : Treatment challenges and promising drug delivery approaches for posterior segment eye diseases, such as age-related macular degeneration (AMD) are summarized. Advances in the development of several nanotechnology-based systems, including stimuli-responsive approaches to enhance drug bioavailability and overcome existing barriers for effective ocular delivery are discussed. Stem cell transplantation and encapsulated cell technology (ECT) approaches to treat posterior eye diseases are elaborated. Expert opinion : There are several drug delivery systems demonstrating promising results. However, a better understanding of ocular barriers, disease pathophysiology, and drug clearance mechanisms is required for better therapeutic outcomes. The stem cell transplantation strategy and ECT approach provide positive results in AMD therapy, but there are a number of challenges that must be overcome for long-term efficiency. Ultimately, there are numerous multidimensional challenges to cure vision problems and a collaborative approach among scientists is required.